High-resolution raster scan optoacoustic mesoscopy of genetically modified drosophila pupae - Omar, Murad; Gateau, Jerome; Ntziachristos, Vasilis (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2014)
Optoacoutic mesoscopy aims to bridge the gap between optoacoustic microscopy and optoacoustic tomography. We have developed a setup for optoacoustic mesoscopy where we use a high frequency, high numerical aperture spherically focused ultrasound transducer, with a wide bandwidth of 25-125 MHz. The excitation is performed using a diode laser capable of >500 μJ/pulse, 1.8ns pulse width, 1.4 kHz pulse repetition rate, at 515 nm. The system is capable to penetrate more than 5 mm with a resolution of 7 μm axially and 30 μm transversally. Using high-speed stages and scanning the transducer in a quasi-continuous mode, a field of view of 2×2 mm2 is scanned in less than 2 minutes. The system is suitable for imaging biological samples that have a diameter of 1-5 mm; zebrafish, drosophila melanogaster, and thin biological samples such as the mouse ear and mouse extremities. We have used our mesoscopic setup to generate 3- dimensional images of genetically modified drosophila fly, and drosophila pupae expressing GFP from the wings, high resolution images were generated in both cases, in the fly we can see the wings, the legs, the eyes, and the shape of the body. In the pupae the outline of the pupae, the spiracles at both ends and a strong signal corresponding to the location of the future wings are observed. © 2014 SPIE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Beam-forming; Epi-illumination; High frequency; Mesoscopy; Microscopy; Optoacoustics